Micropropagation of Labisia pumila using embryo culture - Khairuddin, Muhammad Redhuan; Azhari, Muhammad Ukasyah; Zainuddin, Zarina (Zibeline International, 2020)
Labisia pumila or commonly known as Kacip Fatimah is one of the plants that were used as a medicinal purpose. Previously, several studies on the regeneration of the plant through tissue culture had been conducted. L. pumila can be planted using macropropagation technique in which L. pumila can be propagated by using stem cuttings. However, the seed yields were low. This study was initiated to regenerate L. pumila using micropropagation from the embryo as the explant. Embryos were cultured on different strength MS culture mediums which are full–strength and half–strength whereby the half-strength MS medium was supplemented with 0.5 ppm benzylaminopurine (BAP) for shoot induction. Shoot formation was achieved from both media. High rate of shoot formation occurred on full-strength MS medium without plant growth regulators. Multiple shoots was established on half-strength MS medium containing 0.5 ppm BAP. Shoots elongation and plantlet establishment were produced with culture on half-strength MS medium with combination of 0.5 ppm BA and 0.5 ppm IAA.